Healthcare Professional’s Knowledge about Drug Related Problems in Saudi Arabia - Alomi, Yousef Ahmed; Alaskari, Dima Ahmad; Almelf, Malak Mohammad; Badawi, Dima Ali; Alshihri, Abdullah Mohammad (Journal of Pharmacy Practice and Community Medicine)
Purpose: To explore Healthcare professionals and Knowledge about Drug-related problems in Saudi Arabia. Methods: It is a 4-months cross-sectional survey of healthcare professionals and knowledge of medicines. The survey consisted of two-part, demographic information and second part forty-nine questions divided into four domains. It included domain one: Primary or essential information about healthcare providers medication, domain two: healthcare professionals information about the drug-related problem, domain three: healthcare professionals information about drug-related cost and domain four: Healthcare providers perception of medications. Medline Plus health information and Daily Med-INH elements information from National Institute of Health United State of America were used. The survey distributed through social media by using what’s App to more than one thousand healthcare professionals overall Kingdom of Saudi Arabia. The survey was made in an electronic format, and it analyzed domain two : healthcare professional's information about the drug-related problem through survey monkey system. Results: The total responders were (188) Healthcare professionals. Of those 177 (95.16%) were Saudi and 9 (4.84%) were non-Saudi. The gender distribution 120 (63.83%) were females and 68 (36.17%) were males. The most of Healthcare professionals were pharmacist 93 (71.54%), followed by nurses 18 (13.85%) and physicians 15 (11.54%). The most type of medications used was anti-hypertension medicines, anti-diabetic medicines, Skin medications and drugs for Respiratory Diseases. The healthcare professionals showed good knowledge either complete or incomplete information about the adverse drug reaction either a general side effect of medications 135 (74.2%) or potential adverse event about their medications 128 (69.9%). More than half of responders were familiar with drug overdose behaving 112 (60.86%) or first aid of drug poisoning 112 (61.87%). The responder showed not adequate awareness of contraindication of medicines used with other diseases condition 117 (63.24%), drugs 113 (61.74%), food 119 (64%) or laboratory test 120 (64.51%) and 103 (56.6%) with the herbal drug. The responders showed adequate knowledge either complete or incomplete information about the use of medications for children 131 (71.2%) or elderly 128 (69.56%), drug use during pregnancy 132 (72.1%) or breastfeed 128 (69.56%). Conclusion: One-third of healthcare professionals were not familiar with essential drug-related problems information. It is critical toward drug misadventures and cost burden in the society. Very comprehensive and urgent implementation of the healthcare professional’s education program about medications required in Saudi Arabia.
Keywords: Healthcare professional; Knowledge; Drug-related problems; Ministry of Health; Saudi Arabia